An emended description of Arcobacter anaerophilus Sasi Jyothsna et al. 2013: genomic and phenotypic insights. Issue 6 (11th June 2020) - On, Stephen L. W.; Miller, William G.; Kelly, David J.; Vandamme, Peter
Abstract : Arcobacter anaerophilus was originally described as the first obligate anaerobe in this genus by Sasi Jyothsna et al . 2013. The complete genome sequence of the type strain of this species was determined and analysed. Genes characteristic for organisms capable of aerobic growth were identified, and the ability of the organism to grow under microaerobic and aerobic conditions was confirmed in two independent laboratories. The description of A. anaerophilus is thus emended and the wider ramifications of these findings are discussed.